Steel

A steel material with a tailored chemical composition and specific Ti and V content ratios is used to achieve excellent high-temperature fatigue strength after tempering, addressing the limitations of existing materials in withstanding high temperatures above 500°C.

JP7670970B2Active Publication Date: 2025-05-01NIPPON STEEL CORPORATION
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021170440
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-10-18
Publication Date
2025-05-01
Estimated Expiration
2041-10-18

AI Technical Summary

Technical Problem

Existing steel materials for pistons do not adequately exhibit high-temperature fatigue strength when tempered during the manufacturing process, particularly at temperatures above 500°C.

Method used

A steel material with a specific chemical composition, including C: 0.15-0.50%, Si: 0.01-0.50%, Mn: 0.10-1.00%, P: 0.020% or less, S: 0.028% or less, Cr: 0.50-2.00%, Mo: 0.08-0.50%, V: 0.05-0.50%, Ti: 0.05-0.20%, Al: 0.005-0.100%, N: 0.0200% or less, O: 0.0050% or less, Cu: 0.00-0.50%, Ni: 0.00-1.00%, Nb: 0.000-0.100%, and the remainder Fe and impurities, is used. This composition ensures that the Ti content in the residue is set to [Ti] R, and the V content is set to [V] R, with specific ratios defined by equations (1) and (2) to achieve optimal high-temperature fatigue strength.

Benefits of technology

The steel material exhibits excellent high-temperature fatigue strength after tempering, with the high number density of V precipitates contributing to increased strength even at temperatures of 500-600°C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670970000001
    Figure 0007670970000001
  • Figure 0007670970000002
    Figure 0007670970000002
Patent Text Reader

Abstract

To provide a steel material that exhibits excellent high temperature fatigue strength when a thermal refining treatment is applied during a product manufacturing process as a raw material of a product.SOLUTION: The steel material contains, by mass%, 0.15-0.50% C, 0.01-0.50% Si, 0.10-1.00% Mn, 0.020% or less P, 0.028% or less S, 0.50-2.00% Cr, 0.08-0.50% Mo, 0.05-0.50% V, 0.05-0.20% Ti, 0.005-0.100% Al, 0.0200% or less N, 0.0050% or less O, 0.00-0.50% Cu, 0.00-1.00% Ni, 0.000-0.100% Nb, and a balance Fe with inevitable impurities. A solid solution Ti ratio RTi defined by an expression (1) is 0.30 or less, and a solid solution V ratio RV defined by an expression (2) is 0.60 or more: RTi=([Ti]B-[Ti]R) / [Ti]B (1); and RV=([V]B-[V]R) / [V]B (2).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to steel materials, and more particularly to steel materials suitable for use as materials for products such as steel pistons. [Background technology]

[0002] 2. Description of the Related Art An engine, such as a diesel engine, includes a piston that is housed in a cylinder of the engine and moves back and forth within the cylinder. The piston is exposed to high temperatures during the combustion process while the engine is in operation.

[0003] Many conventional pistons are manufactured by casting aluminum. However, in recent years, there has been a demand for further improvement in engine combustion efficiency. For aluminum cast pistons, the surface temperature of the piston during use is about 240 to 330°C.

[0004] Recently, there has been research into using pistons in even higher combustion temperature ranges to improve combustion efficiency, and so piston materials that can withstand surface temperatures of 400°C or higher, or even 500°C or higher, during use, are in demand.

[0005] In order to meet such demands, steel pistons manufactured using steel materials have begun to be proposed. For example, a steel piston is proposed in Patent Document 1. Steel pistons have a higher melting point than aluminum cast pistons. Therefore, steel pistons can be used in a higher combustion temperature range than aluminum cast pistons.

[0006] Patent Document 2 proposes a technology for increasing the lifespan of a steel piston. Specifically, Patent Document 2 points out the following points regarding the lifespan of a steel piston: During use of a steel piston in a high combustion temperature range, oxide scale forms on the surface of the piston crown of the steel piston. The formed oxide scale peels off from the piston crown, forming scale flaws on the piston crown. These scale flaws (areas where the oxide scale has peeled off) spread, causing cracks to form in the piston crown of the steel piston. To solve this problem, Patent Document 2 forms a protective layer on the piston crown of the steel piston to suppress the formation of oxide scale.

[0007] In the above-mentioned Patent Document 2, a protective layer is formed on the steel piston to extend the life of the steel piston. However, the steel material from which the steel piston is made is not particularly considered.

[0008] Patent Document 3 discloses a steel material that can be used as a material for steel pistons. In the steel material proposed in Patent Document 3, the Mo content and V content in the steel material are adjusted to satisfy a specific formula. As a result, when a steel piston is manufactured using the steel material as a material, a large number of composite carbides of V and Mo are aged and precipitated in the thermal refining treatment during the manufacturing process. These composite carbides increase the high-temperature strength. As a result, the high-temperature fatigue strength of the steel piston is increased. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2004-181534 A [Patent Document 2] JP 2015-078693 A [Patent Document 3] International Publication No. 2019 / 230946 Summary of the Invention [Problem to be solved by the invention]

[0010] The steel material proposed in Patent Document 3 exhibits excellent high-temperature fatigue strength when it is subjected to a thermal refining treatment and made into a product (steel piston). However, it may also exhibit excellent high-temperature fatigue strength when it is subjected to a thermal refining treatment during the manufacturing process of a product as a raw material for the product by a means other than that proposed in Patent Document 3.

[0011] An object of the present disclosure is to provide a steel material that exhibits excellent high-temperature fatigue strength when subjected to thermal refining treatment during the manufacturing process of a product as a raw material for the product. [Means for solving the problem]

[0012] The steel material according to the present disclosure has the following configuration.

[0013] A steel material, Chemical composition, in mass%, C: 0.15-0.50%, Si: 0.01 to 0.50%, Mn: 0.10-1.00%, P: 0.020% or less, S: 0.028% or less, Cr: 0.50~2.00%, Mo: 0.08-0.50%, V: 0.05~0.50%, Ti: 0.05 to 0.20%, Al: 0.005 to 0.100%, N: 0.0200% or less, O: 0.0050% or less, Cu: 0.00-0.50%, Ni: 0.00 to 1.00%, Nb: 0.000 to 0.100%, and The balance: Fe and impurities, It consists of: The Ti content in mass% in the residue obtained by electrolytic extraction is defined as [Ti] R Define it as: The V content in the residue in mass% is [V]R Define it as: The Ti content in mass% in the chemical composition of the steel is [Ti] B Define it as: The V content in mass% in the chemical composition of the steel is [V] B When we define The solute Ti ratio R defined by equation (1) Ti is less than or equal to 0.30, The solute V ratio R is defined by equation (2). V is 0.60 or more, Steel material. R Ti =([Ti] B -[Ti] R ) / [Ti] B (1) R V =([V] B -[V] R ) / [V] B (2) Effect of the Invention

[0014] The steel material according to the present disclosure exhibits excellent high-temperature fatigue strength when subjected to thermal refining treatment during the manufacturing process of a product as a raw material for the product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present inventors first investigated and examined the high-temperature fatigue strength after tempering treatment of steel materials that are used as raw materials for products that are subjected to tempering treatment during the manufacturing process, such as steel pistons.

[0016] First, the present inventors investigated steel materials that exhibit excellent high-temperature fatigue strength after thermal refining treatment from the viewpoint of chemical composition. As a result, the inventors considered that a steel material having a chemical composition, in mass%, of C: 0.15-0.50%, Si: 0.01-0.50%, Mn: 0.10-1.00%, P: 0.020% or less, S: 0.028% or less, Cr: 0.50-2.00%, Mo: 0.08-0.50%, V: 0.05-0.50%, Al: 0.005-0.100%, N: 0.0200% or less, O: 0.0050% or less, Cu: 0.00-0.50%, Ni: 0.00-1.00%, Nb: 0.000-0.100%, and the balance: Fe and impurities may exhibit excellent high-temperature fatigue strength when used as a material for products such as steel pistons and subjected to a thermal refining treatment during the manufacturing process of the product.

[0017] However, even if the ranges of each element in the chemical composition are within the above-mentioned ranges, there are cases where sufficient high-temperature fatigue strength is not obtained in a high-temperature bending fatigue test at a temperature range higher than 500°C. Therefore, the present inventors further investigated means for obtaining high-temperature fatigue strength after the thermal refining treatment. As a result, the present inventors have obtained the following findings.

[0018] When a steel material having the content of each element in the chemical composition within the above-mentioned range is subjected to a tempering treatment, V precipitates are formed by aging. The V precipitates do not melt but remain in the steel material as precipitates even in a high-temperature environment of 500 to 600°C. Therefore, the V precipitates increase the high-temperature fatigue strength of the steel material. The higher the number density of the V precipitates that are formed by aging in the steel material, the higher the high-temperature fatigue strength of the steel material.

[0019] Therefore, the present inventors have investigated a means for age-precipitating a large number of V precipitates in a tempering treatment, and have found that the number density of V precipitates after tempering treatment increases by further adding Ti to a steel material having the above chemical composition in place of a portion of Fe.

[0020] As a result of the inventors' investigations, it was found that if the above-mentioned chemical composition further contains 0.05 to 0.20% Ti instead of part of the Fe, the formation of V precipitates during the tempering treatment is promoted, and excellent high-temperature fatigue strength can be obtained in the steel material (product) after the tempering treatment.

[0021] However, even in the case of a steel material having the above-mentioned chemical composition containing Ti, there are cases in which sufficient high-temperature fatigue strength cannot be obtained after heat treatment. Therefore, the present inventors conducted further research and examination. As a result, the following findings were obtained.

[0022] The Ti content in mass% in the residue obtained by electrolytic extraction is defined as [Ti] R The V content in the residue in mass% is defined as [V] R Furthermore, the Ti content in mass% in the chemical composition of the steel is defined as [Ti] B The V content in mass% in the chemical composition of steel is defined as [V] B In this case, the steel material having the above-mentioned chemical composition is required to satisfy the following two requirements. The solute Ti ratio R defined by equation (1) Ti is 0.30 or less. The solute V ratio R defined by equation (2) V is 0.60 or more. R Ti =([Ti] B -[Ti] R ) / [Ti] B (1) R V =([V] B -[V] R ) / [V] B (2)

[0023] Steel that satisfies the above two requirements exhibits excellent high-temperature fatigue strength after thermal refining. The reason for this is not clear, but the following is thought to be the reason.

[0024] Ti forms fine Ti precipitates in steel material. The Ti precipitates serve as nucleation sites for V precipitates during tempering. Therefore, in order to increase the number density of V precipitates after tempering, it is preferable that a large number of Ti precipitates exist in the steel material before tempering.

[0025] On the other hand, if V precipitates are present in the steel material before the tempering treatment, the V content present as solid solution V during the tempering treatment is reduced, and in this case, the number density of V precipitates precipitated by aging during the tempering treatment is reduced.

[0026] Therefore, in the steel material before the thermal refining treatment, Ti and V are preferably in the following state. (A) Ti is precipitated as Ti precipitates as much as possible. (B) V is made to exist as solid solution V as much as possible, and V precipitates in the steel are reduced as much as possible.

[0027] In the steel material of this embodiment, the solid solution Ti ratio R Ti is 0.30 or less, and the solid solution V ratio R V is set to be 0.60 or more. In this case, the above (A) and (B) can be achieved at the same time. As a result, the number density of V precipitates can be increased in the tempering treatment, and the high-temperature fatigue strength of the steel material (product) after the tempering treatment is improved.

[0028] The steel material for steel pistons according to this embodiment, which has been completed based on the above findings, has the following configuration.

[0029] [1] A steel material, Chemical composition, in mass%, C: 0.15-0.50%, Si: 0.01 to 0.50%, Mn: 0.10-1.00%, P: 0.020% or less, S: 0.028% or less, Cr: 0.50~2.00%, Mo: 0.08-0.50%, V: 0.05~0.50%, Ti: 0.05 to 0.20%, Al: 0.005 to 0.100%, N: 0.0200% or less, O: 0.0050% or less, Cu: 0.00-0.50%, Ni: 0.00 to 1.00%, Nb: 0.000 to 0.100%, and The balance: Fe and impurities, It consists of: The Ti content in mass% in the residue obtained by electrolytic extraction is defined as [Ti] R Define it as: The V content in the residue in mass% is [V] R Define it as: The Ti content in mass% in the chemical composition of the steel is [Ti] B Define it as: The V content in mass% in the chemical composition of the steel is [V] B When we define The solute Ti ratio R defined by equation (1) Ti is less than or equal to 0.30, The solute V ratio R is defined by equation (2). V is 0.60 or more, Steel material. R Ti =([Ti] B -[Ti] R ) / [Ti] B (1) R V =([V] B -[V] R ) / [V] B (2)

[0030] [2] The steel material according to [1], The chemical composition is Cu: 0.01 to 0.50%, Ni: 0.01 to 1.00%, and Nb: 0.001 to 0.100%, Contains one or more elements selected from the group consisting of Steel material.

[0031] The steel material according to this embodiment will be described in detail below. "%" for elements means mass % unless otherwise specified.

[0032] [Features of the steel material of this embodiment] The steel material of this embodiment has the following features 1 and 2. (Feature 1) The content of each element in the chemical composition is within the range described below. (Feature 2) The Ti content in mass% in the residue obtained by electrolytic extraction is defined as [Ti] R Define it as: The V content in the residue in mass% is [V] R Define it as: The Ti content in mass% in the chemical composition of steel is [Ti] B Define it as: The V content in mass% in the chemical composition of the steel is [V] B When we define The solute Ti ratio R defined by equation (1) Ti is less than or equal to 0.30, The solute V ratio R is defined by equation (2). V is 0.60 or more. R Ti =([Ti] B -[Ti] R ) / [Ti] B (1) R V =([V] B -[V] R ) / [V] B (2)

[0033] Features 1 and 2 will be explained below.

[0034] [Feature 1: Chemical composition] The chemical composition of the steel material of this embodiment contains the following elements.

[0035] C: 0.15-0.50% Carbon (C) increases the strength of steel. If the C content is less than 0.15%, this effect cannot be sufficiently obtained even if the contents of other elements are within the ranges of this embodiment. On the other hand, if the C content exceeds 0.50%, the machinability of the steel material decreases even if the contents of other elements are within the ranges of this embodiment. Therefore, the C content is 0.15 to 0.50%. The lower limit of the C content is preferably 0.16%, more preferably 0.17%, further preferably 0.18%, and further preferably 0.19%. The upper limit of the C content is preferably 0.48%, more preferably 0.46%, still more preferably 0.44%, still more preferably 0.42%, and still more preferably 0.40%.

[0036] Silicon: 0.01 to 0.50% Silicon (Si) deoxidizes steel. Silicon also increases the strength of ferrite. If the Si content is less than 0.01%, these effects cannot be sufficiently obtained even if the contents of other elements are within the ranges of this embodiment. On the other hand, if the Si content exceeds 0.50%, the machinability of the steel material decreases even if the contents of other elements are within the ranges of this embodiment. Therefore, the Si content is 0.01 to 0.50%. The lower limit of the Si content is preferably 0.02%, more preferably 0.03%, more preferably 0.04%, more preferably 0.10%, more preferably 0.15%, and more preferably 0.20%. The upper limit of the Si content is preferably 0.45%, more preferably 0.40%, further preferably 0.35%, and further preferably 0.30%.

[0037] Mn: 0.10-1.00% Manganese (Mn) improves the hardenability of steel and also increases the strength of steel by solid solution strengthening. If the Mn content is less than 0.10%, these effects cannot be sufficiently obtained even if the contents of other elements are within the ranges of this embodiment. On the other hand, if the Mn content exceeds 1.00%, the machinability of the steel material decreases even if the contents of other elements are within the ranges of this embodiment. Therefore, the Mn content is 0.10 to 1.00%. The lower limit of the Mn content is preferably 0.12%, more preferably 0.14%, further preferably 0.16%, and further preferably 0.18%. The upper limit of the Mn content is preferably 0.90%, more preferably 0.85%, further preferably 0.80%, and further preferably 0.75%.

[0038] P:0.020% or less Phosphorus (P) is an unavoidable impurity, meaning that the P content is greater than 0%. If the P content exceeds 0.020%, even if the contents of other elements are within the ranges of this embodiment, P segregates at grain boundaries, causing a decrease in the strength of the steel material. Therefore, the P content is 0.020% or less. The lower the P content, the more preferable it is. However, excessive reduction in the P content increases production costs. Therefore, in consideration of industrial production, the lower limit of the P content is preferably 0.001%, and more preferably 0.002%. The upper limit of the P content is preferably 0.019%, more preferably 0.018%, further preferably 0.017%, and further preferably 0.015%.

[0039] S: 0.028% or less Sulfur (S) is unavoidably present, meaning the S content is greater than 0%. S combines with Mn to form Mn sulfides, which improve the machinability of steel. Even if there is even a small amount of S, this effect can be achieved to some extent. On the other hand, if the S content exceeds 0.028%, even if the contents of other elements are within the ranges of this embodiment, coarse Mn sulfides are formed or excessive Mn sulfides are formed, which reduces the high-temperature fatigue strength. Therefore, the S content is 0.028% or less. The lower limit of the S content is preferably 0.001%, more preferably 0.003%, further preferably 0.005%, and further preferably 0.009%. The upper limit of the S content is preferably 0.025%, more preferably 0.023%, more preferably 0.020%, more preferably 0.019%, more preferably 0.018%, and more preferably 0.015%.

[0040] Cr: 0.50~2.00% Chromium (Cr) increases the strength of steel materials. If the Cr content is less than 0.50%, this effect cannot be sufficiently obtained even if the contents of other elements are within the ranges of this embodiment. On the other hand, if the Cr content exceeds 2.00%, even if the contents of other elements are within the ranges of this embodiment, Cr carbides are formed, reducing the high-temperature fatigue strength. If the Cr content exceeds 2.00%, the machinability of the steel material also decreases. Therefore, the Cr content is 0.50 to 2.00%. The lower limit of the Cr content is preferably 0.55%, more preferably 0.60%, further preferably 0.65%, and further preferably 0.70%. The upper limit of the Cr content is preferably 1.90%, more preferably 1.80%, more preferably 1.70%, more preferably 1.60%, and even more preferably 1.50%.

[0041] Mo: 0.08 to 0.50% Molybdenum (Mo) ages and precipitates together with V (described later) in the operating temperature range of steel pistons (500 to 600°C), forming precipitates. This enhances the high-temperature fatigue strength of the steel piston when the engine is in operation. If the Mo content is less than 0.08%, this effect cannot be sufficiently obtained even if the contents of other elements are within the ranges of this embodiment. On the other hand, if the Mo content exceeds 0.50%, even if the contents of other elements are within the ranges of this embodiment, the strength of the steel material becomes excessively high and the toughness decreases. Therefore, the Mo content is 0.08 to 0.50%. The lower limit of the Mo content is preferably 0.09%, more preferably 0.10%, more preferably 0.11%, more preferably 0.12%, and even more preferably 0.13%. The upper limit of the Mo content is preferably 0.46%, more preferably 0.42%, still more preferably 0.38%, still more preferably 0.34%, and still more preferably 0.30%.

[0042] V: 0.05~0.50% Vanadium (V) ages and precipitates together with Mo in the operating temperature range of steel pistons (500 to 600°C), forming precipitates. This enhances the high-temperature fatigue strength of the steel piston when the engine is in operation. If the V content is less than 0.05%, this effect cannot be sufficiently obtained even if the contents of other elements are within the ranges of this embodiment. On the other hand, if the V content exceeds 0.50%, even if the contents of other elements are within the ranges of this embodiment, the strength of the steel material becomes excessively high and the toughness decreases. Therefore, the V content is 0.05 to 0.50%. The lower limit of the V content is preferably 0.07%, more preferably 0.09%, still more preferably 0.11%, and still more preferably 0.13%. The upper limit of the V content is preferably 0.48%, more preferably 0.46%, still more preferably 0.44%, still more preferably 0.42%, and still more preferably 0.40%.

[0043] Ti: 0.05 to 0.20% Titanium (Ti) promotes the formation of V precipitates in a steel piston when the steel piston is manufactured from a steel material. As a result, the high-temperature fatigue strength of the steel piston increases when the engine is in operation. If the Ti content is less than 0.05%, the above effects cannot be sufficiently obtained even if the contents of other elements are within the ranges of this embodiment. On the other hand, if the Ti content exceeds 0.20%, even if the contents of other elements are within the ranges of this embodiment, coarse Ti precipitates remain in the steel piston, and in this case, the high temperature fatigue strength of the steel piston is rather reduced. Therefore, the Ti content is 0.05 to 0.20%. The lower limit of the Ti content is preferably 0.06%, more preferably 0.07%, and further preferably 0.08%. The upper limit of the Ti content is preferably 0.18%, more preferably 0.16%, and further preferably 0.14%.

[0044] Al: 0.005 to 0.100% Aluminum (Al) deoxidizes steel, and if the Al content is less than 0.005%, this effect cannot be obtained even if the contents of other elements are within the ranges of this embodiment. On the other hand, if the Al content exceeds 0.100%, even if the contents of other elements are within the ranges of this embodiment, oxides (inclusions) are generated in excess, and the high-temperature fatigue strength of the steel piston including the HAZ decreases. Therefore, the Al content is 0.005 to 0.100%. The lower limit of the Al content is preferably 0.007%, more preferably 0.008%, still more preferably 0.010%, still more preferably 0.012%, and still more preferably 0.014%. The upper limit of the Al content is preferably 0.090%, more preferably 0.080%, still more preferably 0.070%, still more preferably 0.060%, and still more preferably 0.050%.

[0045] N: 0.0200% or less Nitrogen (N) is an unavoidable impurity. That is, the N content is greater than 0%. If the N content exceeds 0.0200%, the hot workability of the steel material decreases even if the contents of other elements are within the ranges of this embodiment. Therefore, the N content is 0.0200% or less. The upper limit of the N content is preferably 0.0190%, more preferably 0.0180%, further preferably 0.0170%, and further preferably 0.0160%. The N content is preferably as low as possible. However, excessive reduction of the N content increases production costs. Therefore, in consideration of industrial production, the preferred lower limit of the N content is 0.0001%, more preferably 0.0005%, more preferably 0.0010%, and even more preferably 0.0015%.

[0046] O: 0.0050% or less Oxygen (O) is an unavoidable impurity. In other words, the O content is greater than 0%. If the O content exceeds 0.0050%, even if the contents of other elements are within the ranges of this embodiment, excessive oxides are formed, and the high-temperature fatigue strength of the steel piston, including the HAZ, decreases. Therefore, the O content is 0.0050% or less. The upper limit of the O content is preferably 0.0045%, more preferably 0.0040%, more preferably 0.0035%, more preferably 0.0030%, and even more preferably 0.0020%. The O content is preferably as low as possible. However, excessive reduction of the O content increases production costs. Therefore, in consideration of industrial production, the lower limit of the O content is preferably 0.0001%, more preferably 0.0005%, and even more preferably 0.0010%.

[0047] The balance of the chemical composition of the steel material of the present embodiment is composed of Fe and impurities. Here, the impurities refer to components that are mixed in from raw materials such as ore and scrap, or from the manufacturing environment, during industrial production of the steel material, and are not intentionally contained in the steel material.

[0048] The impurities include any element other than the above-mentioned impurities, and may be one element only or two or more elements. Impurities other than those mentioned above include, for example, Ca, B, Sb, Sn, W, Co, As, Pb, Bi, and H. These elements may have the following contents as impurities, for example. Ca:0.0000~0.0005%, B:0.0000~0.0005%, Sb:0.0000~0.0005%, Sn:0.0000~0.0005%, W:0.0000~0.0005%, Co:0.0000~0.0005%, As:0.0000~0.0005%, Pb:0.0000~0.0005%, Bi:0.0000~0.0005%, H:0.0000~0.0005%.

[0049] [About optional elements] The steel material of this embodiment further contains, instead of a part of Fe, Cu: 0.00-0.50%, Ni: 0.00 to 1.00%, and Nb: 0.000~0.100%, Any of these elements increases the strength of a final product when the final product is manufactured using the steel material as a raw material.

[0050] Cu: 0.00~0.50% Copper (Cu) is an optional element and may not be contained, that is, the Cu content may be 0.00%. When contained, Cu improves the hardenability and strength of the steel material. If the Cu content is more than 0.00%, these effects can be obtained to some extent. However, if the Cu content exceeds 0.50%, the hot workability of the steel material decreases even if the contents of other elements are within the ranges of this embodiment. Therefore, the Cu content is 0.00 to 0.50%. The lower limit of the Cu content is preferably 0.01%, more preferably 0.02%, further preferably 0.04%, and further preferably 0.05%. The upper limit of the Cu content is preferably 0.48%, more preferably 0.46%, further preferably 0.44%, and further preferably 0.40%.

[0051] Ni: 0.00~1.00% Nickel (Ni) is an optional element and may not be contained, that is, the Ni content may be 0.00%. When contained, Ni improves the hardenability and strength of the steel material. If the Ni content is more than 0.00%, these effects can be obtained to some extent. However, if the Ni content exceeds 1.00%, even if the contents of other elements are within the ranges of this embodiment, the effect becomes saturated, and furthermore, the raw material cost becomes high. Therefore, the Ni content is 0.00 to 1.00%. The lower limit of the Ni content is preferably 0.01%, more preferably 0.02%, further preferably 0.04%, and further preferably 0.05%. The upper limit of the Ni content is preferably 0.98%, more preferably 0.90%, more preferably 0.85%, more preferably 0.80%, more preferably 0.70%, and more preferably 0.60%.

[0052] Nb: 0.000~0.100% Niobium (Nb) is an optional element and may not be contained, that is, the Nb content may be 0.000%. When Nb is contained, it forms carbides, nitrides, or carbonitrides (hereinafter referred to as carbonitrides, etc.) in the steel material, thereby increasing the strength of the steel material. If the Nb content is more than 0.000%, these effects can be obtained to a certain extent. However, if the Nb content exceeds 0.100%, even if the contents of other elements are within the ranges of this embodiment, the strength of the steel material becomes too high, and the machinability of the steel material decreases. Therefore, the Nb content is 0.000 to 0.100%. The lower limit of the Nb content is preferably 0.001%, more preferably 0.005%, more preferably 0.010%, more preferably 0.015%, and even more preferably 0.020%. The upper limit of the Nb content is preferably 0.095%, more preferably 0.090%, still more preferably 0.085%, still more preferably 0.080%, and still more preferably 0.070%.

[0053] [Method of measuring the chemical composition of steel] The chemical composition of the steel material of this embodiment can be measured by a known composition analysis method. Specifically, chips are collected from the inside of the steel material to a depth of 1 mm or more from the surface using a drill. The collected chips are dissolved in acid to obtain a solution. The solution is subjected to ICP-AES (Inductively Coupled Plasma Atomic Emission Spectrometry) to perform elemental analysis of the chemical composition. The C content and S content are determined by a known high-frequency combustion method (combustion-infrared absorption method). The N content is determined by a known inert gas fusion-thermal conductivity method. The O content is determined by a known inert gas fusion-infrared absorption method.

[0054] The content of each element is determined by rounding off the measured value based on the significant figures defined in this embodiment to the lowest digit of the content of each element defined in this embodiment. For example, the C content of the steel material in this embodiment is defined as a value up to the second decimal place. Therefore, the C content is determined as a value up to the second decimal place obtained by rounding off the third decimal place of the measured value.

[0055] Similarly, the contents of other elements other than the C content of the steel material of this embodiment are determined by rounding off the measured value to the minimum digit specified in this embodiment, and this is the content of that element.

[0056] In addition, rounding off means rounding down if the fraction is less than 5, and rounding up if the fraction is 5 or more.

[0057] (Feature 2) Ratio of solute Ti in steel Ti and solid solution V ratio R V About The steel material of this embodiment further has the following characteristics, provided that the content of each element in the chemical composition is within the range of this embodiment. The Ti content in mass% in the residue obtained by electrolytic extraction is defined as [Ti] R Define it as: The V content in the residue in mass% is [V] R Define it as: The Ti content in mass% in the chemical composition of steel is [Ti] B Define it as: The V content in mass% in the chemical composition of the steel is [V] B When we define The solute Ti ratio R defined by equation (1) Ti is less than or equal to 0.30, The solute V ratio R is defined by equation (2). V is 0.60 or more. R Ti =([Ti] B -[Ti] R ) / [Ti] B (1) R V =([V] B -[V] R ) / [V] B (2) This point will be explained below.

[0058] In the steel material of this embodiment, Ti in the steel material is generated as Ti precipitates as much as possible, and V in the steel material is secured as solid solution V as much as possible. If many Ti precipitates are generated in the steel material and a large amount of V is solid-solubilized, when a final product such as a steel piston is manufactured using the steel material as a raw material, many fine V precipitates are generated by the thermal refining treatment (quenching and tempering) during the manufacturing process. As a result, the high-temperature fatigue strength of the product after the thermal refining treatment is significantly increased. When the content of each element in the chemical composition of the steel material is within the range of this embodiment, the solid solution Ti ratio R defined by formula (1) Tiis 0.30 or less, and the solute V ratio R defined by equation (2) is V If the ratio is 0.60 or more, the high-temperature fatigue strength of the product after the thermal refining treatment is sufficiently increased.

[0059] Therefore, the solute Ti ratio R Ti is 0.30 or less, and the solid solution V ratio RV is greater than or equal to 0.60.

[0060] Solid solution Ti ratio R Ti The upper limit of is preferably 0.28, more preferably 0.26, and even more preferably 0.24. Solid solution Ti ratio R Ti It is preferable that the solute Ti ratio R is as low as possible. Ti may be 0. However, the solute Ti ratio R Ti Therefore, it may be difficult to make the solute Ti ratio R Ti The lower limit of is preferably 0.01, more preferably 0.03, and even more preferably 0.05.

[0061] Solid solution V ratio R V The lower limit of is preferably 0.62, more preferably 0.64, even more preferably 0.66, and even more preferably 0.68. Solid solution V ratio R V It is preferable that the solid solution V ratio R is as high as possible. V However, the solute V ratio R V It may be difficult to make the solid solution V ratio R V The upper limit of is preferably 0.98, more preferably 0.96, even more preferably 0.94, even more preferably 0.92, and even more preferably 0.90.

[0062] [Solute Ti ratio in steel R Ti and solid solution V ratio R V How to determine Ratio of dissolved Ti in steel Ti and solid solution V ratio R Vcan be calculated in the following way: A cylindrical test piece 10 mm in diameter and 15 mm in length is taken from a position at a depth of 1 mm or more from the surface of the steel material.

[0063] In order to remove deposits (surface scale, impurities, etc.) on the surface of the collected cylindrical test specimen, preliminary electrolysis is performed. In preliminary electrolysis, a 10% AA-based solution (a solution containing 10% acetylacetone, 1% tetramethylammonium chloride, and 89% methanol solution by volume fraction) is used to electrolyze about 50 μm from the surface of the cylindrical test specimen at room temperature (20 ± 15°C) and current: 1000 mA.

[0064] The cylindrical test piece after preliminary electrolytic polishing is immersed in an alcohol solution. The cylindrical test piece immersed in the alcohol solution is subjected to ultrasonic cleaning to remove any deposits on the surface of the cylindrical test piece. The mass of the cylindrical test piece after ultrasonic cleaning (the cylindrical test piece before constant current electrolysis) is measured.

[0065] Next, constant current electrolysis is performed on the cylindrical test piece. Specifically, a new 10% AA-based solution is prepared. Then, using the new 10% AA-based solution, constant current electrolysis is performed at room temperature with a current density of 20 mA / cm. 2 The cylindrical test piece is held at this temperature and a region from the surface to a depth of about 100 μm is electrolyzed.

[0066] After the constant current electrolysis, the cylindrical test piece is immersed in an alcohol solution. Then, ultrasonic cleaning is performed to remove the deposits on the surface of the cylindrical test piece. After the constant current electrolysis, the mass of the cylindrical test piece from which the deposits have been removed is measured.

[0067] The 10% AA solution used in the constant current electrolysis and the alcohol solution used in the subsequent ultrasonic cleaning are suction filtered through a filter with a mesh size of 0.2 μm to extract the residue.

[0068] The extracted residue is dissolved in acid to obtain a solution. Chemical elemental analysis is performed on the solution using ICP-AES to obtain the mass of Ti in the residue and the mass of V in the residue. Furthermore, the mass of the cylindrical test piece before and after galvanostatic electrolysis is subtracted to obtain the mass of the steel bar electrolyzed at constant current. Based on the mass of Ti in the residue and the mass of the steel bar electrolyzed at constant current, the Ti content in the residue in mass% [Ti] is calculated. R Based on the mass of V in the residue and the mass of the steel bar electrolyzed at constant current, the V content in the residue in mass% [V] is calculated. R Request.

[0069] The Ti content in the chemical composition of the steel obtained by the above-mentioned well-known composition analysis method [Ti] B and Ti content in the residue [Ti] R Using the above, the solute Ti ratio R defined by equation (1) is Ti Similarly, the V content in the chemical composition of the steel [V] B and the V content in the residue [V] R Using the above, the solid solution V ratio R defined by equation (2) is V Request.

[0070] [Effects of the steel material of this embodiment] The steel material of this embodiment has the above-mentioned features 1 and 2. Therefore, when a product such as a steel piston is manufactured using the steel material of this embodiment as a material, the high-temperature fatigue strength of the product can be improved.

[0071] [Use of the steel material according to this embodiment] The steel material of this embodiment can be applied as a material for products manufactured by performing thermal refining treatment. The steel material of this embodiment is particularly suitable as a material for products that require high-temperature fatigue strength. One example of such a product is a steel piston. However, the steel material of this embodiment can be widely applied to applications other than steel pistons.

[0072] [Microstructure of the steel material of this embodiment]

[0073] The microstructure of the steel material of this embodiment is not particularly limited. When the steel material of this embodiment is used as a material for a product such as a steel piston, the steel material is subjected to the following steps during the manufacturing process of the product: c3 The steel material is heated to a temperature equal to or higher than the transformation point. Therefore, the microstructure of the steel material of the present embodiment is not particularly limited.

[0074] As an example of the microstructure of the steel material of this embodiment, at the R / 2 position of a cross section (transverse section) perpendicular to the longitudinal direction of the steel material, the area ratio of bainite is 60% or more, and the remainder is one or more of ferrite, pearlite, and martensite. Here, the R / 2 position means the center position of the line segment R (i.e., the radius) connecting the center of the steel material and the surface of the steel material in the transverse section. However, the microstructure of the steel material of this embodiment is not particularly limited to the above-mentioned microstructure.

[0075] [Manufacturing method] An example of a method for manufacturing a steel material according to this embodiment will be described. The method for manufacturing a steel material described below is one example for manufacturing a steel material according to this embodiment. Therefore, a steel material having the above-mentioned configuration may be manufactured by a manufacturing method other than the manufacturing method described below. However, the manufacturing method described below is a preferred example of a method for manufacturing a steel material according to this embodiment.

[0076] An example of a method for manufacturing a steel material according to this embodiment includes the following steps. (Process 1) Material preparation process (Process 2) Hot processing process The hot working process includes the following two steps: (Step 21) Heating step 1st heating step: Heating temperature T1:900~1100℃ Holding time at heating temperature T1: 20 minutes or more Second heating step: Heating temperature T2: Over 1100~1300℃ Holding time at heating temperature T2: 10 minutes or more (Step 22) Processing process Finish rolling temperature FT: 900℃ or higher Average cooling rate CR from finishing rolling temperature FT to 500°C: 1.0°C / sec or more Each step will be described below.

[0077] [(Process 1) Material preparation process] In the material preparation process, molten steel in which the content of each element in the chemical composition falls within the range of this embodiment is produced by a known steelmaking method. The produced molten steel is used to produce a slab by a continuous casting method. Here, the slab is, for example, a bloom or a billet. Instead of the slab, an ingot may be produced by an ingot casting method using the molten steel. A material (slab or ingot) is produced by the above production process.

[0078] [(Process 2) Hot processing process] In the hot working process, the produced material is hot worked to produce steel. In the hot working process, one or more hot working steps are usually performed. When multiple hot working steps are performed, the first hot working step (rough working step) is, for example, blooming or hot forging. The next hot working step (finishing working step) is, for example, finish rolling using a continuous rolling mill. In the continuous rolling mill, a horizontal stand having a pair of horizontal rolls and a vertical stand having a pair of vertical rolls are alternately arranged in a row.

[0079] The rough machining step may be omitted. In other words, the hot working step may only include the finish machining step. If the material prepared in the material preparation step is a bloom or an ingot, the rough machining step is performed to manufacture a billet. If the material prepared in the material preparation step is a billet, the rough machining step is omitted and the finish machining step is performed.

[0080] As described above, the finish processing step during the hot working step includes the following steps: (Step 21) Heating step (Step 22) Processing process Each step will be described below.

[0081] [(Step 21) Heating step] In the heating process, the billet is heated using a continuous heating furnace. The continuous heating furnace is, for example, a walking beam furnace. In the continuous heating furnace, a plurality of billets are arranged from the charging port toward the extraction port. The plurality of billets advance from the charging port to the extraction port over time. At this time, the billets are arranged so that the longitudinal direction of the billet is perpendicular to the billet advancement direction. The billet is charged into the heating furnace from the charging port of the heating furnace and moves within the heating furnace. Then, when the billet reaches the extraction port, the billet is transported from the extraction port to the outside of the heating furnace. The transported billet is transported to a continuous rolling mill that performs finish rolling by a transport mechanism such as a transport roller.

[0082] In the heating process, two-stage heating is performed in a heating furnace. Specifically, the first heating process is performed, and then the temperature is raised to perform the second heating process. By performing two-stage heating, Ti precipitates in the billet are sufficiently dissolved in the heating process. In this case, fine Ti precipitates are sufficiently generated in the steel material after the processing process, which is the next process, provided that other manufacturing conditions are satisfied. Therefore, the solute Ti ratio in the steel material can be set to 0.30 or less. The first heating process and the second heating process will be described below.

[0083] [First heating step] In the first heating step, the billet is held in a heating furnace at the next heating temperature T1 (° C.) for a holding time t1 (minutes). Heating temperature T1:900~1100℃ Holding time at heating temperature T1: 20 minutes or more In short, in the first heating step, the billet is heated in a heating furnace in a temperature range of 900 to 1100° C. for 20 minutes or more. When the heating temperature T1 is less than 900°C or the holding time t1 is less than 20 minutes, Ti precipitates in the billet do not dissolve sufficiently. In this case, fine Ti precipitates are not sufficiently formed in the steel material after the processing step. As a result, the solute Ti ratio in the steel material after manufacturing exceeds 0.30. If the heating temperature T1 is set to 900 to 1100°C and the holding time is set to 20 minutes or more, Ti precipitates in the billet will be sufficiently dissolved in the heating process, provided that other manufacturing conditions are satisfied. Therefore, fine Ti precipitates will be sufficiently formed in the steel material after the processing process, provided that other manufacturing conditions are satisfied.

[0084] The upper limit of the retention time t1 is not particularly limited. In consideration of the production cost, the upper limit of the retention time t1 is preferably, for example, 120 minutes.

[0085] [Second heating process] In the heating furnace, the billet after the first heating step is heated and the second heating step is performed. In other words, the billet after the first heating step is not cooled and then the second heating step is performed, but the billet after the first heating step is further heated and the second heating step is performed.

[0086] In the second heating step, the billet is held in the heating furnace at the next heating temperature T2 (° C.) for a holding time t2 (minutes). Heating temperature T2: Over 1100~1300℃ Holding time at heating temperature T2: 10 minutes or more In short, in the second heating step, the billet is heated in a temperature range of more than 1100° C. to 1300° C. for 10 minutes or more. When the heating temperature T2 is more than 1100 to 1300°C and the holding time t2 is less than 10 minutes, Ti precipitates in the billet do not dissolve sufficiently even if the conditions in the first heating step are satisfied. In this case, fine Ti precipitates are not sufficiently formed in the steel material after the processing step. Therefore, the solute Ti ratio in the steel material after production exceeds 0.30. If the heating temperature T2 is set to more than 1100 to 1300°C and the holding time is set to 10 minutes or more, Ti precipitates in the billet will be sufficiently dissolved, provided that other manufacturing conditions are satisfied. Therefore, fine Ti precipitates will be sufficiently generated in the steel material after the processing step, provided that other manufacturing conditions are satisfied.

[0087] The upper limit of the heating temperature T2, 1300° C., is a well-known temperature. The upper limit of the holding time t2 is not particularly limited. If the manufacturing cost is to be reduced, the preferable upper limit of the holding time t2 is, for example, 100 minutes.

[0088] As described above, by performing two-stage heating (first heating step and second heating step) in the heating step, the Ti precipitates in the billet can be sufficiently dissolved. Therefore, fine Ti precipitates can be uniformly dispersed in the steel material in the processing step. As a result, the solute Ti ratio R Ti can be set to 0.30 or less.

[0089] [(Step 22) Processing process] In the processing step, the billet after the heating step is subjected to hot processing (hot rolling) using a continuous rolling mill to produce a steel material. The continuous rolling mill includes a plurality of rolling stands. The plurality of rolling stands are arranged in a line. The billet is reduced (rolled) by the plurality of rolling stands to produce a steel material of a predetermined size. The processing step satisfies the following conditions: Finish rolling temperature FT: 900℃ or higher Average cooling rate CR from finishing rolling temperature FT to 500°C: 1.0°C / sec or more The finishing rolling temperature FT and the average cooling rate CR are the solute V ratio R V Affects.

[0090] If the finish rolling temperature FT is less than 900°C, V precipitates will form during the finish rolling. V is less than 0.60. Therefore, the finish rolling temperature FT is set to 900°C or higher. The lower limit of the finish rolling temperature FT is preferably 920°C, more preferably 940°C, and further preferably 960°C. The upper limit of the finish rolling temperature FT is not particularly limited. The finish rolling temperature FT depends on the heating temperature T2 in the heating step. When the heating temperature T2 is 1100 to 1300°C, the upper limit of the finish rolling temperature FT is, for example, 1100°C.

[0091] If the average cooling rate CR is less than 1.0°C / sec, V precipitates will precipitate at the phase interface during the cooling process. V is less than 0.60. Therefore, the average cooling rate CR is 1.0°C / sec or more. The lower limit of the average cooling rate CR is preferably 2.0° C. / sec, and more preferably 3.0° C. / sec. The upper limit of the average cooling rate CR is not particularly limited. The upper limit of the average cooling rate CR is, for example, 15.0° C. / sec, for example, 12.0° C. / sec.

[0092] The steel material of this embodiment can be manufactured by the above steps.

[0093] [Manufacturing method of steel pistons] An example of a method for manufacturing a steel piston using the steel material of the present embodiment described above will be described.

[0094] A method for manufacturing the steel piston of this embodiment is, for example, as follows. Hot forging process → Thermal treatment process → Joining process → Machining process

[0095] Specifically, hot forging is performed on the steel material of this embodiment, which is a raw material, to manufacture the upper and lower members, which are intermediate products (hot forging process). The heating temperature of the steel material during hot forging is 1100 to 1250° C. Here, the heating temperature means the furnace temperature of the heating furnace.

[0096] As mentioned above, the heating temperature of the steel material in the hot forging process is 1100 to 1250°C, but the holding time at the heating temperature is short. Therefore, in the intermediate product after hot forging, the solid solution Ti ratio R Ti is almost maintained.

[0097] The manufactured upper and lower parts are subjected to a known thermal refining treatment (quenching and tempering) (thermal refining treatment process). The quenching treatment is performed at a known quenching temperature (A 3 The quenching is performed at a temperature above the transformation point, followed by quenching. The quenching is performed, for example, by water quenching or oil quenching. The tempering process is also performed at a known tempering temperature (AC1 The test is carried out at a temperature below the transformation point.

[0098] The upper and lower members after the thermal refining process are subjected to well-known friction welding or laser welding to manufacture a joined product in which the upper and lower members are joined (joining process). The joined product is then subjected to machining such as cutting (machining process) to manufacture the final product, a steel piston.

[0099] In addition, after the hot forging process and before the tempering process, the upper member and / or the lower member may be cut. Also, after the tempering process and before the joining process, the upper member and / or the lower member may be cut.

[0100] A steel piston manufactured using the steel material of this embodiment has excellent high-temperature fatigue strength. In addition, among steel pistons, the upper member may be manufactured using the steel material of this embodiment as a material, and the lower member may be manufactured using an alloy other than the steel material of this embodiment. Also, the lower member may be manufactured using the steel material of this embodiment as a material, and the upper member may be manufactured using an alloy other than the steel material of this embodiment. In short, the steel material of this embodiment may be used for at least one of the upper and lower members constituting a steel piston. EXAMPLES

[0101] Steel materials having the chemical compositions shown in Table 1 were manufactured.

[0102] [Table 1]

[0103] In Table 1, "-" means that the content of the corresponding element is 0% in the significant figures (numbers to the least significant digits) specified in the embodiment. In other words, it means that the content of the corresponding element is 0% when the fraction in the significant figures (numbers to the least significant digits) specified in the above embodiment is rounded off.

[0104] For example, the Cu content is a value up to the second decimal place as specified in this embodiment. Therefore, the Cu content of test number 1 is 0.00% after rounding off the third decimal place. Similarly, the Nb content is a value up to the third decimal place as specified in this embodiment. Therefore, the Nb content of test number 1 is 0.000% after rounding off the fourth decimal place.

[0105] Blooms were produced by continuous casting using the molten steel of each test number. The produced blooms were subjected to a rough processing step to produce billets. Specifically, the blooms were subjected to blooming to produce billets. The heating temperature of the blooms before blooming for each test number in the rough processing step was 1000 to 1200°C. The billets produced in the rough processing step were air-cooled to room temperature.

[0106] Next, the billets were subjected to a finishing process. Specifically, the billets of each test number were subjected to a heating process (first heating process, second heating process). Table 2 shows the heating temperature T1 (℃) and holding time t1 (min) in the first heating process, and the heating temperature T2 (℃) and holding time t2 (min) in the second heating process.

[0107] [Table 2]

[0108] In test number 30, the first heating step was not performed, and only the second heating step was performed. That is, in test number 30, one-stage heating was performed in the finish processing step. In test numbers other than test number 30, two-stage heating (first heating step and second heating step) was performed.

[0109] The billet after the heating process was subjected to finish rolling (processing process) using a continuous rolling mill. The finish rolling temperature FT (°C) for each test number was as shown in Table 2. Furthermore, the average cooling rate CR (°C / sec) from the finish rolling temperature FT to 500°C was as shown in Table 2. Through the above manufacturing process, a steel material, which is a steel bar having a diameter of 40 mm, was manufactured.

[0110] [Evaluation test] The following evaluation tests were carried out using the steel materials (steel bars) having the respective test numbers thus produced. (Test 1) Chemical composition measurement test of steel (Test 2) Ratio of solute Ti in steel R Ti and solid solution V ratio R V Decision test (Test 3) High temperature fatigue strength evaluation test Each test will be explained below.

[0111] [(Test 1) Steel chemical composition measurement test] The chemical composition of the steel material of each test number was analyzed based on the method described in [Method of measuring chemical composition of steel material] above. As a result, the chemical composition of the steel material of each test number was as shown in Table 1.

[0112] [(Test 2) Solid solution Ti ratio in steel R Ti and solid solution V ratio R V Decision test] The above-mentioned [Solute Ti ratio in steel R Ti and solid solution V ratio R V Based on the method for determining the Ti content in the residue [Ti] R , and V content in the residue [V] R asked for. Furthermore, the Ti content in the chemical composition of the steel obtained in Test 1 [Ti] B and Ti content in the residue [Ti] R Using the above, the solute Ti ratio R defined by equation (1) is Ti Similarly, the V content in the chemical composition of the steel [V] was calculated. B and the V content in the residue [V] R Using the above, the solid solution V ratio R defined by equation (2) is Vasked for. Obtained Ti content [Ti] R , V content [V] R , solid solution Ti ratio R Ti , and the solid solution V ratio R V is shown in Table 2.

[0113] [(Test 3) High temperature fatigue strength evaluation test] The manufacturing process of a steel piston was simulated, and the following manufacturing process was carried out using the steel material with each test number to prepare a high-temperature Ono-type rotating bending fatigue test specimen simulating a steel piston.

[0114] Specifically, a 40 mm diameter steel bar of each test number was heated at 1200°C for 30 minutes. The heated steel bar was hot forged to produce a 30 mm diameter round bar. The finishing temperature in hot forging was 950°C or higher for all test numbers.

[0115] The round bar after hot forging was subjected to a thermal refining treatment. Specifically, the round bar was heated at a heating temperature of 950°C for one hour, and then immersed in an oil bath at an oil temperature of 80°C for quenching treatment. The quenched round bar was subjected to a tempering treatment. In the tempering treatment, the quenched round bar was held at a heating temperature of 600°C for one hour, and then cooled in the air.

[0116] A high-temperature Ono-type rotating bending fatigue test piece was prepared from the center of the cross section perpendicular to the axial direction (longitudinal direction) of the tempered round bar. The central axis of the high-temperature Ono-type rotating bending fatigue test piece was approximately the same as the central axis of the tempered round bar. The diameter of the parallel part of the high-temperature Ono-type rotating bending fatigue test piece was 8 mm, and the length of the parallel part was 15.0 mm.

[0117] Using the prepared high-temperature Ono-type rotating bending fatigue test pieces, high-temperature Ono-type rotating bending fatigue tests were carried out under the following conditions. The evaluation temperature was 550°C. After the test piece was attached to the test machine in the heating furnace, the furnace was started to heat up while rotating at 2500 rpm. After the furnace temperature gauge reading reached 550°C, the test piece was soaked at 550°C for 30 minutes. After soaking, a load was applied and the fatigue test was started. The stress ratio is set to -1, and the maximum number of repetitions is 1×10 7 The maximum number of repetitions (1 × 10 7 The endurance stress of the fatigue test (number of times) was defined as the fatigue strength (MPa). The fatigue strength (MPa) obtained for each test number is shown in Table 2. If the fatigue strength was 250 MPa or more, it was determined that excellent high-temperature fatigue strength was obtained.

[0118] [Test Results] The test results are shown in Tables 1 and 2.

[0119] The steel materials of test numbers 1 to 20 satisfied features 1 and 2. Therefore, the fatigue strength obtained in the high-temperature fatigue strength evaluation test was 250 MPa or more, and excellent high-temperature fatigue strength was obtained in the test pieces simulating the steel piston.

[0120] On the other hand, the V content of the steel material of test number 21 was too low. Therefore, the fatigue strength obtained in the high-temperature fatigue strength evaluation test was less than 250 MPa, and the high-temperature fatigue strength of the test piece simulating the steel piston was low.

[0121] In the steel material of test number 22, the Ti content was too low. Therefore, the fatigue strength obtained in the high-temperature fatigue strength evaluation test was less than 250 MPa, and the high-temperature fatigue strength of the test piece simulating the steel piston was low.

[0122] The Ti content of the steel material of test number 23 was too high. As a result, the fatigue strength obtained in the high-temperature fatigue strength evaluation test was less than 250 MPa, and the high-temperature fatigue strength of the test piece simulating the steel piston was low.

[0123] In the steels of test numbers 24 and 25, the heating temperature T1 in the first heating step of the finishing process was low. Ti As a result, the fatigue strength obtained in the high-temperature fatigue strength evaluation test was less than 250 MPa, and the high-temperature fatigue strength of the test piece simulating the steel piston was low.

[0124] In the steel material of test number 26, the holding time t1 at the heating temperature T1 in the first heating step of the finishing process was short. Therefore, the solute Ti ratio R Ti As a result, the fatigue strength obtained in the high-temperature fatigue strength evaluation test was less than 250 MPa, and the high-temperature fatigue strength of the test piece simulating the steel piston was low.

[0125] In the steels of test numbers 27 and 28, the heating temperature T2 in the second heating step of the finishing process was low. Ti As a result, the fatigue strength obtained in the high-temperature fatigue strength evaluation test was less than 250 MPa, and the high-temperature fatigue strength of the test piece simulating the steel piston was low.

[0126] In the steel material of test number 29, the holding time t2 at the heating temperature T2 in the second heating step of the finishing process was short. Ti As a result, the fatigue strength obtained in the high-temperature fatigue strength evaluation test was less than 250 MPa, and the high-temperature fatigue strength of the test piece simulating the steel piston was low.

[0127] For the steel material of test number 30, the first heating step of the finishing process was not carried out, and only the second heating step was carried out. Ti As a result, the fatigue strength obtained in the high-temperature fatigue strength evaluation test was less than 250 MPa, and the high-temperature fatigue strength of the test piece simulating the steel piston was low.

[0128] In the steels of test numbers 31 and 32, the finishing temperature FT in the finishing process was low. Therefore, the solid solution V ratio R V As a result, the fatigue strength obtained in the high-temperature fatigue strength evaluation test was less than 250 MPa, and the high-temperature fatigue strength of the test piece simulating a steel piston was low.

[0129] In the steels of test numbers 33 and 34, the average cooling rate CR in the finishing process was slow. Therefore, the solute V ratio RV As a result, the fatigue strength obtained in the high-temperature fatigue strength evaluation test was less than 250 MPa, and the high-temperature fatigue strength of the test piece simulating a steel piston was low.

[0130] The embodiments of the present invention have been described above. However, the above-described embodiments are merely examples for carrying out the present invention. Therefore, the present invention is not limited to the above-described embodiments, and the above-described embodiments can be appropriately modified and carried out without departing from the spirit of the present invention.

Claims

1. A steel material, The chemical composition, in mass%, is C: 0.15-0.50%, Si: 0.01 to 0.50%, Mn: 0.10-1.00%, P: 0.020% or less, S: 0.028% or less, Cr: 0.50-2.00%, Mo: 0.08-0.50%, V: 0.05-0.50%, Ti: 0.05-0.20%, Al: 0.005-0.100%, N: 0.0200% or less, O: 0.0050% or less, Cu: 0.00-0.50%, Ni: 0.00-1.00%, Nb: 0.000 to 0.100%, and The balance: Fe and impurities, It consists of: The Ti content in mass% in the residue obtained by electrolytic extraction is [Ti] R Define it as: The V content in the residue in mass% is [V] R Define it as: The Ti content in mass% in the chemical composition of the steel material is [Ti] B Define it as: The V content in mass% in the chemical composition of the steel material is [V] B When we define The solute Ti ratio R defined by the formula (1) Ti is 0.30 or less, The solute V ratio R defined by the formula (2) V is 0.60 or more, Steel material. R Ti =([T] B -[T] R ) / [T] B (1) R V =([V] B -[V] R ) / [V] B (2)

2. The steel material according to claim 1, The chemical composition is Cu: 0.01 to 0.50%, Ni: 0.01 to 1.00%, and Nb: 0.001 to 0.100%, Contains one or more elements selected from the group consisting of Steel material.

Citation Information

Patent Citations

  • High-strength steel superior in delayed-fracture resistance

    JP2003253376A

  • Method for producing piston for internal combustion engine and engine obtained from this producing method

    JP2004181534A

  • Age-hardenable steel and method for manufacturing machine part

    JP2012193416A

  • Steel piston for internal combustion engine and its manufacturing method

    JP2015078693A

  • Age hardening steel

    JP2017066460A